O IMPACTO DE PERCEPÇÃO DE SUPORTE ORGANIZACIONAL E COMPROMETIMENTO ORGANIZACIONAL AFETIVO SOBRE A INTENÇÃO DE ROTATIVIDADE - Silva, Rogério dos Santos (2014)
The aim of this study was to analyze, interpret and discuss the relationship between perceived organizational support, affective organizational commitment and turnover intention and the effect of variables: gender, age, seniority and leadership on turnover intention. The study included 132 workers who work in the state of São Paulo in public and private organizations. As a tool for data collection, a self-administered questionnaire consists of three scales that measured variables were used. This research was aimed to present, interpret and discuss the relationships between variables, but also test the hypotheses concerning the proposed conceptual framework, through a cross-cutting research with quantitative approach, which collected data were analyzed by applying techniques parametric statistics (calculation of descriptive statistics: mean, standard deviation, student t test, correlation and multivariate statistical calculations: analysis of hierarchical multiple regression). The processing and analysis of data were performed by the statistical software Statistical Package for Social Sciences - SPSS, version 19.0 for Windows. The results showed that perceived organizational support and organizational commitment are direct predictors of turnover intention. Variables: gender, age, seniority and leadership showed no significant regression coefficients, therefore we can t state that are antecedents of turnover intention. The results were discussed in light of literature in the field, having been compared with results from other empirical studies.